THE ROLE OF BANKS IN DIGITALIZATION OF THE ECONOMY - Adilova Zohida Ikromjonovna (Journal of Artificial Intelligence and Digital Economy, 2024)
Being an important factor in ensuring the solvency of banks in the conditions of digitalization of the economy, it is a necessary condition for ensuring the continuity of payments made in the country's economy. In the article, current problems related to the role of banks in the digitalization of the economy are identified and scientific proposals aimed at solving them are developed.